'(Text as) wording' as wording in text size: stretching lexicogrammatical rank hierarchy from clause to text. Issue 2 (3rd April 2017) - Peng, Xuanwei
Abstract : This paper attempts to argue for the hypothesis that, in Systemic Functional Linguistics, the topmost rank of lexicogrammar should be 'text' or 'discourse' rather than the widely accepted view of 'clause (complex)'; that is, it aims to demonstrate the following two points: (i) the rank scale hierarchy of language should be extended upward from 'clause (complex)' to 'text (type)', from morpheme to text being a continuum; and (ii) text meaning and text wording, which should then be of equal size, form an integral whole in complementarity. It follows that a model of text arises with multi-dimensions. The attempt provides a way to better understanding the nature of text and language, both from the system and instance perspectives.